IMPROVED DESIGN OF CIRCULAR SAW WITH COMBINED GEAR CROWN FOR LONGITUDINAL SAWING OF WOOD - Pylypchuk, M.I.; Shostak, V.V.; Taras, V.I.; Salovskyy, S.A.; Ditkovskyy, M.V. (Forestry, Forest, Paper and Woodworking Industry, 2019)
A new design of circular saw with hard alloy plates has been developed, its gear crown is made in two sizes of straight pointed teeth FZ1 / FZ2, alternating through one: one (slit) has a thickness equal to the thickness of the saw body and the height of the other (scraper) is less than 1.5 mm and has a thickness equal to the width of the saw. The influence of the structural parameters of the saw with combined teeth FZ1 / FZ2 on the accuracy of longitudinal sawing of wood is explained by the special design of the saw, which is divided into two stages: initially, cut tooth FZ1 cuts the middle part of the chips, forming a groove at the bottom of the saw, which holds the saw; next is FZ2 blade, which forms the left and right part of the saw at the same time, extending the formed groove to a given width of the saw. The design of the circular saw with straight sharpened cut and clean teeth FZ1 / FZ2 and a protrusion of cut teeth FZ1 1.5 mm above the cutting circle ensures straight cut and sufficiently high tool resistance in the saw with a minimum thickness of a saw blade equal o1.6 mm. The use of FZ1 / FZ2 saw reduces the width of the saw by 1.7 times compared to the classic saw with FZ teeth and, thus, reduces the energy consumption of the process and, by simplifying the design, makes the saw preparation for work less complex. Proceeding from the results of the experimental research, it is established that the saw blade with FZ1 / FZ2 combination gear wheel, under the conditions of a rational sawing mode, ensures a precision of machining within ± 0.5 mm and allows to reduce wood and electricity losses.